Health Promotion Model to Increase Maternal Visit and Exclusive Breastfeeding in the Puerperium Period in Sleman, Yogyakarta - Eny Retna Ambarwati; Endang Khoirunnisa; Waryana - (Journal of Health Promotion and Behavior, 2016)
Background: Exclusive breastfeeding in the puerperium period is beneficial for mother and infant. Breastfeeding stimulate oxytocin release that will increase uterine contraction. It in turn fastens uterine involution process and eventually prevents prolonged post partum bleeding. Breastfed infants are healthier, have better nutritional status, and less probability of dying. Therefore, there is a need to develop a health promotion model that empowers post partum mothers to visit maternity clinic for post partum examination. This study aimed to determine factors that affect maternal visits to maternity clinic for post partum examination.Subjects and Method: This was an analytical observational study with cross-sectional design. This study was conducted in Sleman, Yogyakarta. A total sample of 125 post partum mothers was selected for this study. The dependent variable was number of visits to maternity clinic for post partum examination. The independent variables were maternal knowledge, access to information, husband support, stakeholder role, and participation in maternal health promotion class. The data were collected by a set of questionnaire, and then were analyzed by Structural Equation Model (SEM).Results: The SEM showed Goodness of Fit, with indicators as follows: Chi Square 263.01, p= 0.055, RMSEA=0.025, GFI=0.98, NFI=0.92, and CFI 1.00. Maternal knowledge (b=0.15), access to information (b=0.42), husband support (b=0.52), stakeholder role (b=0.57), participation in maternal health promotion class (b=0.04).Conclusion: Maternal knowledge, access to information, husband support, stakeholder role, participation in maternal health promotion class, are important determinant of maternal visit to maternal clinic for post partum examination.Keywords: maternal visit, maternal clinic, health promotion class, puerperium.Correspondence: Eny Retna Ambarwati. Academyof Midwifery Yogyakarta, Yogyakarta,Indonesia. Email: enyretnaambarwati@gmail.com.Journal of Health Promotion and Behavior (2016), 1(3): 138-148https://doi.org/10.26911/thejhpb.2016.01.03.01